Spectroscopic and Structural Properties of β-Tricalcium Phosphates Ca9RE(PO4)7 (RE = Nd, Gd, Dy) - Veronica Paterlini; Asmaa El Khouri; Marco Bettinelli; Daniele Maria Trucchi; Francesco Capitelli (Crystals, 2021)
Rare-earth-based Ca9RE(PO4)7 (RE = Nd, Gd, Dy) materials were synthesized by solid-state reaction at T = 1200 °C. The obtained tricalcium phosphate (TCP) materials are efficient light emitters due to the presence of RE3+ ions, although these ions are present at high concentrations. Moreover, in these host structures, these ions can be used as optical probes to study their local environments. Thus, photoluminescence (PL) emission spectra of the powder samples clearly indicated, for Dy3+ and Gd3+ ions, the presence of the RE3+ ion in low-symmetry sites with some local structural disorder, and the spectra show the presence of vibrational features (in the case of Gd3+). For the Nd3+ phase, emission bands are present around 900, 1050, and 1330 nm, originating from the 4F3/2 level. In general, these RE-TCP samples are interesting luminescent materials in the visible (Dy), UV (Gd), and NIR (Nd) regions, due to weak concentration quenching even for high concentrations of the emitting ion.